Pharmacokinetics and clinical effects of xylazine and dexmedetomidine in horses recovering from isoflurane anesthesia. Issue 4 (12th March 2020) - Guedes, Alonso; Knych, Heather; Tucker, Laura; Almeida, Daniel C.; Baldo, Caroline F.; Wendt‐Hornickle, Erin; Allweiler, Sandra
Abstract: This study determined the pharmacokinetics and compared the clinical effects of xylazine and dexmedetomidine in horses recovering from isoflurane anesthesia. Six healthy horses aged 8.5 ± 3 years and weighing 462 ± 50 kg were anesthetized with isoflurane for 2 hr under standard conditions on two occasions one‐week apart. In recovery, horses received 200 μg/kg xylazine or 0.875 μg/kg dexmedetomidine intravenously and were allowed to recover without assistance. These doses were selected because they have been used for postanesthetic sedation in clinical and research studies. Serial venous blood samples were collected for quantification of xylazine and dexmedetomidine, and the pharmacokinetic parameters were calculated. Two individuals blinded to treatment identity evaluated recovery quality with a visual analog scale. Times to stand were recorded. Results (mean ± SD ) were compared using paired t tests or Wilcoxon signed‐ranked test with p < .05 considered significant. Elimination half‐lives (62.7 ± 21.8 and 30.1 ± 8 min for xylazine and dexmedetomidine, respectively) and steady‐state volumes of distribution (215 ± 123 and 744 ± 403 ml/kg) were significantly different between xylazine and dexmedetomidine, whereas clearances (21.1 ± 17.3 and 48.6 ± 28.1 ml/minute/kg), times to stand (47 ± 24 and 53 ± 12 min) and recovery quality (51 ± 24 and 61 ± 22 mm VAS) were not significantly different. When used for postanesthetic sedation following isoflurane anesthesia in healthy horses, dexmedetomidine displays faster plasma kinetics but is not associated with faster recoveries compared to xylazine.